MANAJEMEN PEMBELAJARAN DISCOVERY LEARNING PADA BIDANG STUDI ILMU PENGETAHUAN SOSIAL BERBASIS KURIKULUM 2013 - Firmansyah Firmansyah (UNIVERSITAS BENGKULU, 2015)
The purpose of this study is to analyze the management of the implementation of the learning model discovery learning on social science subjects based curriculum in 2013 on SMPN1Curup. The method is descriptive qualitative research. The subjects of this study is subject teachers in charge of the Social Sciences in SMP N 1 Curup. Methods of data collection are interviews, observation, and documentation. From these results, it shows that management is executed in a learning model Discovery Learning in the field of social studies curriculum 2013 based on SMPN 1 Curup, has done well, which includes activities; learning planning, learning implementation, and evaluation of learning.Key word: management, discovery learning model, social studies